Raymond, Chase Wesley y Olguín, Luis Manuel, Análisis de la Conversación: fundamentos, metodología y alcances. Londres & Nueva York: Routledge. 2022. 235 pp. ISBN 978-1-138-58052-7 - Batlle Rodríguez, Jaume (Discurso & Sociedad, 2023)
Raymond, Chase Wesley y Olguín, Luis Manuel, Análisis de la Conversación: fundamentos, metodología y alcances. Londres & Nueva York: Routledge. 2022. 235 pp. ISBN 978-1-138-58052-7.